Influence of Cultivars and Cultivation Land Slope on Sensory Quality of Gayo Arabica Coffee - Abubakar, Yusya'; Hasni, Dian; Widayat, Heru Prono; Muzaifa, Murna; Rinaldi, Dedi (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractAll processes involved influence the quality of brewed coffee. One factor that has not been explored well is the influence of environmental conditions, such as cultivation land slopes. This research examines the influence of cultivation area position on the taste quality of coffee from three local cultivars commonly cultivated in the Gayo Highlands. This research used a factorial randomized block design consisting of 2 factors: cultivar (V) and land area (H). The cultivars (V) observed were V1 = Timtim, V2= Borbor, V3 = Ateng Super, and V4 = multi variety. The expanse of coffee cultivation land (H) consists of M1 = flat expanse of land and M2 = sloping expanse of land with a slope of 25%-35%. The experiment was carried out with three replications. The results showed that the coffee brew from Ateng Super had higher acidity (low pH value, 4.90) than the other two cultivars. Cupping test results show that sloping land tends to produce better-tasting coffee brews. Borbor planted on sloping land produces coffee with the highest cupping score. The total cupping score for all treatments ranged from 80,04 – 85,08 with mean value 83,89, which shows that the coffee in this study meets the category of specialty coffee based on the standards of the Specialty Coffee Association of America (SCAA).Keywordss: arabica, coffee, cupping test, Gayo Highland, quality AbstrakMutu seduhan kopi sebagai produk akhir sangat dipengaruhi sejak awal proses hingga penyeduhan. Salah satu faktor yang belum terkesplorasi dengan baik adalah pengaruh kondisi lingkungan, seperti kemiringan lahan tanam. Penelitian ini bertujuan untuk mengkaji pengaruh posisi hamparan lahan tanam terhadap kualitas cita rasa kopi dari tiga kultivar lokal yang umum dibudidayakan di Dataran Tinggi Gayo. Penelitian ini menggunakan Rancangan Acak Kelompok Faktorial yang terdiri dari 2 faktor, yaitu kultivar (V) dan hamparan lahan (H). Kultivar (V) yang diamati adalah V1 = Timtim, V2 = Borbor dan V3 = Ateng Super dan V4 = multivarietas. Hamparan lahan tanam kopi (H) terdiri dari M1 = hamparan lahan datar, dan M2 = hamparan lahan miring dengan tingkat kemiringan 25-35%. Eksperimen dilakukan dengan 3 (tiga) ulangan. Hasil penelitian menunjukkan bahwa seduhan kopi dari Ateng Super memiliki keasaman tinggi (nilai pH rendah, 4,90) dibandingkan dua kultivar lainnya. Hasil uji cita rasa menunjukkan bahwa hamparan lahan miring cenderung menghasilkan seduhan kopi bercita rasa lebih baik. Borbor yang ditanam pada lahan miring menghasilkan seduhan kopi dengan cupping score tertinggi. Total cupping score semua perlakuan berkisar80,04-85,08 dengan rerata 83,89 yang menunjukkan bahwa kopi yang dihasilkan dalam penelitian ini masuk dalam katagori kopi specialty berdasarkan standar Specialty Coffee Association of America (SCAA).Kata kunci: arabika, cupping test, dataran tinggi Gayo, kopi, kualitas